Speculations V : aesthetics in the 21st century - Askin, Ridvan; Ennis, Paul J. (Editor); Hägler, Andreas; Schweighauser, Philipp (Punctum Books, 2014)
"Ever since the turn of the century aesthetics has steadily gained momentum as a central field of study across the disciplines. No longer sidelined, aesthetics has grown in confidence. While this recent development brings with it a return to the work of the canonical authors (most notably Baumgarten and Kant), some contemporary scholars reject the traditional focus on epistemology and theorize aesthetics in its ontological connotations. It is according to this shift that speculative realists have proclaimed aesthetics as "first philosophy" and as speculative in nature. With speculative realism aesthetics no longer necessarily implies human agents. This is in alignment with the general speculative realist framework for thinking all kinds of processes, entities, and objects as free from our all-pervasive anthropocentrism, which states, always, that everything is "for us." This special volume of Speculations explores the ramifications of what could be termed the new speculative aesthetics. In doing so, it stages a three-fold encounter: between aesthetics and speculation, between speculative realism and its (possible) precursors, and between speculative realism and art and literature"--